Análise funcional da proteína 14-3-3 de Paracoccidioides brasiliensis e prospecção de alvos terapêuticos inibidores da interação de P. brasiliensis à pneumócitos - Assato, Patricia Akemi [UNESP] (2014)
Paracoccidioidomycosis (PCM) a systemic mycosis endemic in Latin America, with high prevalence in Brazil, has as etiological agent dimorphic fungi Paracoccidioides spp., P. brasiliensis e P. lutzii. During the infection process the adhesins, substances synthetized by fungi that interacts with host's extracellular matrix (ECM), are important virulence factors for the establishment of infection. A 30kDa protein that belongs to 14-3-3 proteins family stands out in the adhesion process of this fungus. The 14-3-3 proteins are present in all eukaryotic cells and play multiple functions. In P. brasiliensis, the 14-3-3Pb protein binds to lamin, the major component of ECM from host cells, and during the infection the expression is increased. In order to have a better understanding of 14-3-3Pb functions the aim of this study is to perform a functional analysis of this protein through achieving a functional homologous in S. cerevisiae and to analyze the monoclonal antibody anti-14-3-3Pb during infection. S. cerevisiae was chosen as model because it's widely use in genetic research, unlike P. brasiliensis, and has two isoforms of 14-3-3 proteins, Bmh1p and Bmh2p, with high identity with 14-3-3Pb. The functional homologous were obtained by yeast transformation of pYES-14-3-3Pb vector. Complementation assay was performed with obtained transformants, and it was observed that 14-3-3Pb partially complements Bmh1p and Bmh2p, with higher complementation of Bmh2p. Also susceptibility assays were performed with antifungal drugs and semi-synthetic compounds derived from gallic acid where it was observed that S. cerevisiae wild type was less sensitive to antifungals than the knockout strains, S. cerevisiae Δbmh1 and Δbmh2. Monoclonal antibody anti14-3-3Pb was evaluated alone and in association with substances with antifungal activities through inhibition adhesion assay, where it was observed that the anti-14-3-3Pb alone is able to inhibit P. brasiliensis ...